(3QjGOI GdCYeGd hGdeTQhYGJ GdUZjQI (B:s (3eaghe GdeHGOQI (B- (3GSJQGJjLjI GdeHGOQI (B- (3JMdjd GdaQU GdeMdjI hGdOhdjI (B/s - (3YHGS, YdGAs; (3GdSdGej, eMeO s ((3GdEScfOQjI(B: s (3OGQ GdJYdje GdLGeYj(B, s)
(3JfGhd gPG GdcJGH ehVhY QjGOI GdCYeGd hGdeTQhYGJ GdUZjQI ef NdGd GdJWQb Gddi eaghe hGSJQGJjLjI GdeHGOQI hWQjbI JacjQ GdeHGOQ , HGdGVGaI Gdi JMOjO hJMdjd GdaQU GdeMdjI hGdOhdjI s
Keywords: (3EOGQI GdCYeGds; (3GdeTQhYGJs